COVID-19 PANDEMIC : ONLINE LEARNING PLATFORMS FOR ELEMENTARY SCHOOLS - Taufiqulloh Dahlan; Darta Darta; Trian Pamungkas Alamsyah; Irawati Sri Wardhani (JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
AbstractThis research uses survey and descriptive methods. The purpose of this research is to identify the role of parents in online learning in elementary schools with various platforms that have been used. The population in this research were the parents of elementary school students. The sampling usedwas purposive sampling from the parents of Cikapundung 2 Elementary School and Palalangon Elementary School as many as 100 respondents. The data collection technique used was a Google form questionnaire. The results showed that 71% used WhatsApp application as the online learning media, 15% used Google classroom application, 8% used the Zoom application, and 6% used television. Thus, online learning at Palalangon Elementary School and Cikapundung 2 Elementary School are uses various platforms including WhatsApp, Google Classroom, Zoom, and Television.Keywords: Online Learning; Role of Parents